PENERAPAN MARKETING MIX PADA STRATEGI KOMUNIKASI PEMASARAN KAIN BATIK BESUREK DALAM MEMPERTAHANKAN EKSISTENSI KAIN BESUREK: (Studi pada Swarnabumei, Galeri Kain Batik Besurek diKota Bengkulu ) - Gigin Pasan Dani; Sri Dwi Fajarini (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2022)
This study aims to describe the Marketing Communication Strategy of the batik gallery of Besurek Swarnabumei. This type of research is descriptive research with a qualitative approach. The data collection method used consisted of the interview method, the observation method, and the document method. The data analysis used consisted of data reduction, data presentation and conclusion drawing. The results showed that the batik gallery of Besurek Swarnabumei in introducing and maintaining the existence of its products to the public uses an integrated marketing communication strategy that aims to increase the company's sales. The marketing communication strategy used is advertising through print media, electronic media, and internet media. Personal selling activities are carried out by the owners and employees of the Besurek Swarnabumei batik gallery. Sales promotions are carried out by giving discounts and participating in activities held by local governments or national events. A good relationship is also established by the batik gallery of Besurek Swarnabumei, both with the community and consumers with the aim of getting a good image from the community. In addition, producers also market their products directly to the public without going through distributors or intermediaries. Marketing via the internet is also carried out by the batik gallery of Besurek Swarnabumei, namely through Instagram and Facebook. Keywords: Strategy, Marketing Communication, Existence, Batik Besurek